Empowering Distributed Solar PV Energy for Malaysian Rural Housing: Towards Energy Security and Equitability of Rural Communities - N.A. Ahmad; H. Byrd (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
This paper illustrates on how Malaysia’s development landscapes has been poweredby cheap oil and gas making it dependent and addicted on using large amounts of fossil fuels. As acountry that is primarily depended on fossil fuels for generating power supply, Malaysia needs tocogitate of long-term energy security due to fossil fuel depletion and peak oil issues. Loss of theseresources could leadto thereduction of power generation capacitywhich will threaten the stabilityof the electricity supply in Malaysia. This could potentially influence in an increase in electricitycosts which lead to a phase of power scarcity and load shedding for the country. With the risk ofinterrupted power supplies, rural households, especially those of low-income groups areparticularly vulnerable to the post-effects of a power outage and an inequitable distribution to thepeople. Distributed generation of electricity by solar PVs diminishes the vulnerability of thesehouseholds and can also offer an income to them by feeding the power supply to the national gridthrough Feed-in Tariff scheme. At the moment, the deployment of solar PV installations is still inthe introductory stage in Malaysia, where roof-mounted PV panels are only available to commercialand urban residential buildings. This is due to the lack of a suitable renewable energy policy forrural households and the high cost of the solar PV technology. This paper will put forward ananalysis for incorporating solar photovoltaic on roofs of rural houses by identifying the energyconsumption of these households and the extent to which PVs can alleviate electricity insecurity.The results present significant potential for distributed PV power generation in rural areas inMalaysia which shown a considerable amount of electricity needed to be harvested from roofmountedsolar PV for rural people in Malaysia.